The Aghria : a peasant caste on a tribal frontier - Skoda, Uwe (New Delhi : Manohar : Distributed in South Asia by Foundation Books, 2005)
On the Agaria, Indic people from Orissa; a study.
Originally presented as the author's thesis (Ph. D.--Institute of Ethnology, Free University of Berlin).
Includes bibliographical references (p. [583]-596) and index.
Keywords: AGARIA (INDIC PEOPLE) -- INDIA -- ODISHA -- HISTORY; ODISHA (INDIA) -- HISTORY